1993
DOI: 10.1164/ajrccm/148.3.637
|View full text |Cite
|
Sign up to set email alerts
|

KL-6, a Mucin-like Glycoprotein, in Bronchoalveolar Lavage Fluid from Patients with Interstitial Lung Disease

Abstract: KL-6, a mucin-like high-molecular-weight glycoprotein, is a serum marker indicating the disease activity of pneumonitis, such as idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis, and sarcoidosis. Immunohistochemical studies have shown that KL-6 is strongly expressed on Type 2 pneumocytes and also exists on epithelial cells in other organs. It has not been clarified whether the increased levels of KL-6 in sera from patients with pneumonitis are derived from the lower respiratory tract. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 252 publications
(185 citation statements)
references
References 28 publications
2
181
1
Order By: Relevance
“…The high-molecular-weight pulmonary epithelial mucin KL-6 is an integral membrane glycoprotein that appears to be predominantly expressed on injured and/or activated alveolar type II cells (19). Recently, we reported that the localization of KL-6 protein appeared primarily on the apical surface of alveolar type II cells in postmortem ARDS patients (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-molecular-weight pulmonary epithelial mucin KL-6 is an integral membrane glycoprotein that appears to be predominantly expressed on injured and/or activated alveolar type II cells (19). Recently, we reported that the localization of KL-6 protein appeared primarily on the apical surface of alveolar type II cells in postmortem ARDS patients (1).…”
Section: Discussionmentioning
confidence: 99%
“…This glycoprotein is mainly expressed on alveolar type II cells in the lung (20) and is expressed more prominently on proliferating, regenerating, or injured type II cells than on normal type II cells (19,20). The presence of KL-6 has been used to monitor severity of disease in idiopathic pulmonary fibrosis (19).…”
mentioning
confidence: 99%
“…KL-6's value in diagnosing patients with ILDs compared to healthy controls has been demonstrated by several studies (8,9). The clinical cut-off value for distinguishing patients with ILDs from healthy subjects and patients with lung diseases other than ILDs had been set at the level of 500 U/mL (10).…”
Section: Kl-6mentioning
confidence: 99%
“…Levels of KL-6 in BALF were reported to be consistent with those in serum (5,8,9), whereas the levels of SP-A and SP-D in BALF were reported to be inversely correlated with levels in serum (19)(20)(21). Although the levels of KL-6, SP-A and SP-D in BALF are potential biomarkers for IPF, the inconvenience of obtaining BALF has resulted in their limited use clinically.…”
Section: Osteopontinmentioning
confidence: 99%
“…Several studies have measured the levels of KL-6, SP-A, and SP-D in the bronchoalveolar lavage fluid (BALF) of IPF patients in attempt to understand how those levels become elevated (14)(15)(16). It has been thought that the destruction of the alveolar epithelium and endothelium might cause hyperlucent blood.…”
Section: Introductionmentioning
confidence: 99%